The impact of crude oil price on Islamic stock indices of South East Asian countries: evidence from MGARCH-DCC and wavelet approaches - Abdullah, Ahmad Monir; Saiti, Buerhan; Masih, Mansur (Elsevier, 2016)
This paper is the first attempt at testing the ‘time-varying’ and ‘time-scale dependent’ volatilities of and correlations between the selected Islamic stock indices of South East Asian countries and selected commodities for enhancing portfolio diversification benefits. Consistent with the results of our VECM, our analysis based on the application of the recent wavelet technique MODWT, indicates that the Singapore Islamic index is leading the other Islamic indices and the commodities. From the point of view of portfolio diversification benefits, based on the extent of dynamic correlations between variables, our results suggest that an investor should be aware that the Philippine Islamic stock index is less correlated with the crude oil in the short run (as evidenced in the continuous wavelet transform analysis) and that an investor holding the crude oil can gain by including the Malaysian Islamic stock index in the portfolio (as evidenced in the Dynamic conditional correlation analysis).